Perancangan Program Berbasis Web Pada Penjualan Bahan Bangunan - Andika Sulis Pratama; Ida Darwati (JURNAL TEKNIK KOMPUTER AMIK BSI, 2017)
Computers are devices that are now widely used by the public to facilitate a job, such as data processing that can be transferred from the processing manually into computerization. When a set of computers connected to the internet it can provide many benefits such as communication media, promotions and sales transactions online. Like the sale of building materials, sales that already utilize the internet then its promotions and transactions can reach a large area and can be done anytime, without the buyer having to come directly to the store building.